2015
DOI: 10.1245/s10434-015-4903-7
|View full text |Cite
|
Sign up to set email alerts
|

Clinicopathologic Analysis of PD-L1 and PD-L2 Expression in Renal Cell Carcinoma: Association with Oncogenic Proteins Status

Abstract: PD-L1 and PD-L2 expression predict poor prognosis in CCRCC. Thus, PD-1/PD-L pathway-targeted immunotherapy may be useful for treatment of patients with CCRCC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
122
1
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 161 publications
(139 citation statements)
references
References 28 publications
14
122
1
2
Order By: Relevance
“…PD-L2 can bind to the RGMb receptor on the surface of macrophages and other immune cells to promote immune tolerance, although the significance of this observation in cancer is unclear (51). PD-L2 expression has been noted in esophageal adenocarcinoma, breast cancer, and renal cell cancer (35,(52)(53)(54). The significance of PD-L2 expression on epithelial cells is less explored, compared with PD-L1 expression.…”
Section: Discussionmentioning
confidence: 99%
“…PD-L2 can bind to the RGMb receptor on the surface of macrophages and other immune cells to promote immune tolerance, although the significance of this observation in cancer is unclear (51). PD-L2 expression has been noted in esophageal adenocarcinoma, breast cancer, and renal cell cancer (35,(52)(53)(54). The significance of PD-L2 expression on epithelial cells is less explored, compared with PD-L1 expression.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, different proportions of PD-L1 expression ranging from 9.4 to 56 % PD-L1 positive RCC specimens were reported [15,36,37]. Also, variation in quantitative and qualitative PD-L1 expression was reported among primary and metastatic RCC sites, as well as in dependence of the histological subtype [17,29,30,37]. Krambeck et al evaluated the impact of survivin and PD-L1 expression in 298 ccRCC specimens.…”
Section: Discussionmentioning
confidence: 99%
“…Leite et al [15] published a series of 115 ccRCC specimens wherein 56 % of the specimens showed PD-L1 expression, which in combination with microvascular invasion and a higher nuclear grade is associated with severe prognosis. Recently, going along with findings of the largest analyses of all subtypes of RCC (n = 425), Iacovelli et al performed a meta-analyses suggesting a prognostic role of PD-L1 in RCC [19,37]. Nonetheless, the authors of this analysis underlined the significant heterogeneity of the included studies as potential bias [19].…”
Section: Discussionmentioning
confidence: 99%
“…The mean H-score of the five areas was calculated for each case, and mean H-scores were calculated separately for the epithelioid and sarcomatoid components of sRCC. As a quality control measure, two pathologists (FK and KS) manually evaluated PD-L1 tumor positivity, defined as ≥5% tumor cell membrane staining independently 9, 10 . Cases in which the H-score differed from the results of manual evaluation, owing to diffuse infiltration of PD-L1–stained immune and endothelial cells in the tumor area and cytoplasmic PD-L1 staining of tumor cells, were excluded from the study.…”
Section: Methodsmentioning
confidence: 99%
“…In addition, PD-L1 induces epithelial-mesenchymal transition in RCC 7 and sRCC is considered a good example of epithelial-mesenchymal transition both morphologically and immunohistochemically 8 . Two studies evaluated PD-L1 expression in sRCC with clear cell epithelioid component (cc-sRCC) and found it to be significantly higher than in non-sarcomatoid ccRCC 9, 10 . Furthermore, 50% of sRCCs showed co-expression of PD-1/PD-L1, while only 3% of non-sarcomatoid ccRCCs showed PD-1/PD-L1 co-expression 9 .…”
Section: Introductionmentioning
confidence: 99%